ANALISIS PENGARUH SUHU DAN LAMA PEMANASAN MINYAK DEDAK PADI TERHADAP TINGKAT KADAR AIR DAN TEGANGAN TEMBUS - Rizal, Mohammad Iqbal Fakhrur; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
This journal discusses the effect of heating with various temperature and duration variations on rice bran oil regarding its moisture content and breakdown voltage, aiming to be used as an alternative liquid insulation oil in high-voltage equipment. Oil purification through heating is conducted to reduce the moisture content in rice bran oil with temperature variations of 40°C, 50°C, 60°C, and 70°C, and duration variations of 15 minutes, 30 minutes, 45 minutes, and 60 minutes. Electrical testing (using AC breakdown voltage test circuit with capacitive voltage divider method) and physical testing (moisture content reduction test using oven heating method (gravimetric)) are performed to determine the feasibility of rice bran oil as an alternative liquid insulation oil. The test results showed that the breakdown voltage of pure rice bran oil was 17,39 kV/2,5 mm, which did not meet the SPLN 49 standard of 1982, which is 30 kV/2,5 mm before processing. Heating the rice bran oil successfully increased the breakdown voltage to 56,26 kV/2,5 mm, achieved when the oil was treated with a heating temperature of 70°C and a heating duration of 60 minutes. It was found that heating the rice bran oil could reduce its moisture content from 1130 ppm to 624,92 ppm. Thus, it can be concluded that heating significantly affects the moisture content and breakdown voltage of rice bran oil. In terms of moisture content, rice bran oil does not yet meet the maximum standard allowed by SPLN 49 of 1982, which is 30 ppm. However, in terms of breakdown voltage, rice bran oil after heating meets the SPLN 49 standard of 1982, which is 50 kV/2,5 mm after processing. Keywords: Insulation oil, rice bran oil, moisture content, breakdown voltage.